2020
DOI: 10.1159/000508834
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Serum Adipolin with Epicardial Fat Thickness and Severity of Coronary Artery Diseases in Acute Myocardial Infarction and Stable Angina Pectoris Patients

Abstract: Objective: Adipolin/C1q/TNF-related protein-12 is a family of CTRPs highly expressed in adipose tissue with glucose-lowering and anti-inflammatory effects. Various risk factors have been suggested in the incidence of cardiovascular diseases, such as a decrease in anti-inflammatory or an increase in inflammatory factors. The purpose of the present study was to investigate the correlation of adipolin with anthropometric, angiographic, echocardiographic, and biochemical parameters. Subject and Methods: A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Although the exact mechanism of EFT in the pathogenesis of patients with CAD is unknown, EFT appears to be involved in the pathogenesis of atherosclerosis with paracrine/ endocrine effects (35). In a previous study, a relationship was shown between EFT and some parameters, such as the Gensini score, LVEF, and WBC (24). In general, the EFT is thought to play a key role in the pathogenesis of the disease in patients with CAD that requires further studies.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Although the exact mechanism of EFT in the pathogenesis of patients with CAD is unknown, EFT appears to be involved in the pathogenesis of atherosclerosis with paracrine/ endocrine effects (35). In a previous study, a relationship was shown between EFT and some parameters, such as the Gensini score, LVEF, and WBC (24). In general, the EFT is thought to play a key role in the pathogenesis of the disease in patients with CAD that requires further studies.…”
Section: Discussionmentioning
confidence: 97%
“…Evidence from animal and human studies has shown that adipose tissue (AP) plays a critical role in some chronic inflammatory diseases, such as cardiovascular disease, rheumatoid arthritis, asthma, and COPD (5,6,24). Moreover, the AP is of utmost importance in the pathogenesis of the disease by activating autocrine/paracrine/endocrine pathways to release a variety of chemical mediators, such as adipolin, visfatin, leptin, fatty acid-binding protein-4, and nesfatin-1 (6,24,26). Nesfatin-1 has been initially recognized as a satiety hormone, as its intracerebroventricular injection in the animal study led to decreased food intake (8).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations